Opening Up Efficiency: A Deep Dive into Property Management in Zanzibar’s Commercial Hubs - Said Saida Abdalla; Lucian Charles Alibaho (Baltic Journal of Real Estate Economics and Construction Management)
This study evaluates the performance of property management practices for commercial properties in Zanzibar, focusing on financial performance, operational efficiency, and tenant satisfaction. Using a case study approach, four properties, which are M/Kwerekwe Shopping Centre, Michenzani Mall, Chawl Building, and Thabit Kombo Building, were assessed. The research employed a mixed-methods design, incorporating quantitative and qualitative data collected through surveys, interviews, and document reviews. Findings indicate significant operational efficiency and tenant satisfaction challenges despite reasonable financial performance. Income collection efficiency varied across properties, with rates ranging from 21.9 % to 51.5 %, averaging 41.25 %, indicating challenges in revenue collection. Operational efficiency ratings were low across parameters such as the speed of service delivery, the quality of maintenance, and the cost efficiency. Tenant satisfaction was also low, with frequent complaints about maintenance delays and poor communication.